Furin Expression in Patients With Psoriasis—A Patient Cohort Endangered to SARS-COV2? - Graier, Thomas; Golob-Schwarzl, Nicole; Weger, Wolfgang; Benezeder, Theresa; Painsi, Clemens; Salmhofer, Wolfgang; Wolf, Peter (Frontiers in Medicine, 2021)
Background: SARS-Cov2 has raised concerns among dermatologists regarding psoriasis and its respective treatments. Comorbidities, which induce the expression of the proprotease furin have been associated with severe course of COVID-19. Furin and angiotensin converting enzyme 2 (ACE2) play a major role in viral host cell entry of SARS-Cov2. Objective: To evaluate expression of Furin and ACE2 from blood cells in psoriasis patients, and whether systemic or topical treatment reduces expression levels. Methods: This observational translational study analysed blood samples from patients from two clinical trials. Furin and ACE2 expression levels were analysed prior to systemic or topical treatment, as well as 3 and 12-24 months after start of biologic treatment with either ustekinumab or secukinumab. Additionally, the study analysed expression levels 6 days after start of dithranol treatment and 4-6 weeks after end of dithranol treatment. Results: Furin expression was significantly increased at baseline in the biologic (4.92.6 fold change, p<0.0001) and in the dithranol group (2.71,4 fold change, p<0.001) compared to controls. There was a trend for arthritis patients to express more furin than patients with psoriatic skin involvement only (5.262.30 versus 3.482.27, p=0.078). Analysing furin mRNA expression after treatment initiation with secukinumab or ustekinumab revealed a normalization of levels after 3 and 12 to 24 months. Similar findings were obtained for patients treated with dithranol, with significantly decreased expression levels 6 days after start of dithranol treatment and also at follow-up, (4-6 weeks after dithranol treatment had been terminated). ACE2 expression levels did not differ from controls at any timepoint, regardless of biologic or topical treatment. Conclusion: Significantly overexpressed levels of furin were observed in untreated patients, and, thus, these patients may be at risk for infection and a severe course of COVID-19. However, the data indicate that successful therapeutic intervention in psoriasis, by systemic biologic or topical treatment, can efficiently reduce furin levels in blood cells, possibly limiting the risk of psoriasis patients for a severe COVID-19 course. Trial registration: Clinical Trials.gov no. NCT02752672